Diffuse Large B-cell Lymphoma of the Prostate: Case Study of an Uncommonly Encountered Entity. (9th November 2022) - Harbert, J; Chen, J; Fakhri, N; Bhalla, R; Rinker, E
Abstract: Introduction/Objective: Hematologic neoplasms comprise less than 1% of prostate malignancies, with diffuse large b-cell lymphoma (DLBCL) accounting for 15% of those. Chronic lymphocytic leukemia/small lymphocytic lymphoma is most often seen, comprising 53% of lymphomas at this site, with the remainder consisting of marginal zone, mantle cell, and follicular lymphomas. Methods/Case Report: Our case involves a 51-year-old African American male presenting to a medium-sized academic medical center with a chief complaint of hematuria with clot retention. Patient did endorse night sweats and chills at this time. Imaging revealed an 11 cm mass involving the prostate and bladder, a 10 cm right adrenal mass, and pelvic lymphadenopathy. A cystoscopy with transurethral resection was performed with tissue histology showing complete effacement of prostatic parenchyma by sheets of medium-sized, mildly irregular, non-cohesive cells with minimal cytoplasm. Tissue morphology appeared highly suspicious for lymphoma, but the rarity of this process along with the possibility of other lesions led to differential diagnoses including small cell carcinoma, poorly differentiated prostatic adenocarcinoma, high-grade urothelial carcinoma, and granulomatous prostatitis. Immunohistochemical staining of neoplastic cells showed CD20+ B cells with a non-germinal center immunophenotype (CD10-) and co-expression of Bcl-2 and c-myc. Subsequent FISH analysis demonstrated a Bcl-6 gene rearrangement without a Bcl-2 or MYC rearrangement. Ki67 was positive in 90% of tumor cells. Rituximab-cyclophosphamide-doxorubicin-vincristine-prednisone was initiated for stage IV DLBCL with prophylactic intrathecal methotrexate. The patient has received 6 cycles of chemotherapy to date with resolution of the prostate and adrenal masses. Bladder involvement is still seen radiographically, but is suspected to be mainly necrotic tissue. Results (if a Case Study enter NA): N/A Conclusion: Less aggressive lymphomas are more common, which makes this presentation additionally unexpected. We employed a wide battery of immunohistochemical stains, including NKX3.1, s100, gata-3, pan-ck, CD68, and chromogranin and synaptophysin, when initially evaluating the neoplastic tissue.